Biological correlates of altered circadian rhythms, autonomic functions and sleep problems in autism spectrum disorder - Liliana Dell’Osso; Leonardo Massoni; Simone Battaglini; Ivan Mirko Cremone; Claudia Carmassi; Barbara Carpita (Annals of General Psychiatry, 2022)
Abstract Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by a complex and multifaceted neurobehavioral syndrome. In the last decades, several studies highlighted an increased prevalence of sleep problems in ASD, which would be associated with autonomic system and circadian rhythm disruption. The present review aimed to summarize the available literature about sleep problems in ASD subjects and about the possible biological factors implicated in circadian rhythm and autonomic system deregulation in this population, as well as possible therapeutic approaches. Shared biological underpinnings between ASD symptoms and altered circadian rhythms/autonomic functions are also discussed. Studies on sleep showed how ASD subjects typically report more problems regarding insufficient sleep time, bedtime resistance and reduced sleep pressure. A link between sleep difficulties and irritability, deficits in social skills and behavioral problems was also highlighted. Among the mechanisms implicated, alteration in genes related to circadian rhythms, such as CLOCK genes, and in melatonin levels were reported. ASD subjects also showed altered hypothalamic pituitary adrenal (HPA) axis and autonomic functions, generally with a tendency towards hyperarousal and hyper sympathetic state. Intriguingly, some of these biological alterations in ASD individuals were not associated only with sleep problems but also with more autism-specific clusters of symptoms, such as communication impairment or repetitive behaviors Although among the available treatments melatonin showed promising results, pharmacological studies for sleep problems in ASD need to follow more standardized protocols to reach more repeatable and reliable results. Further research should investigate the issue of sleep problems in ASD in a broader perspective, taking into account shared pathophysiological mechanisms for core and associated symptoms of ASD.